Developing iot-based “saf” straightener monitoring system prototype for congregational prayers using arduino as a microcontroller / Zahari Abu Bakar … [et al.] - Abu Bakar, Zahari; Omar, Mastura; Mat Saat, Ezril Hisham; Misnan, Mohamad Farid; Ahmad, Mohd Farhan; Mohamad Radzi, Mohamad Ezzat Saifuddin; Elias, Eqmal Mirza (Universiti Teknologi MARA, 2021)
Performing prayer five times a day such as Subuh, Zuhur, Asar, Maghrib and Isyak is a compulsory thing that Muslims need to do. One of the problem soccurred during congregational prayers is to straighten the “saf”. Some of the reasons why Muslims do not straighten their “saf” are they are as late for prayer in congregation, lack of knowledge about the importance of straightening “saf” during congregation prayers etc. Prophet Muhammad S.A.W did emphasized on straintening “saf” during congregational prayer because it is considered as a part of the perfection of prayer. An urgent innovation is needed in order to help all Muslims to understand better of the needs of straightening their “saf” in every prayer. This project is developed in order to build a prototype of “saf” straightening indicator that will help to straighten the “saf” during congregational prayers and to develop a program for monitoring “saf” alignment during congregational prayers. This prototype was built using Arduino Mega as a microcontroller, lasers and LDR as input sensors, Bluetooth as a switch and LED, LCD and buzzer as outputs. This prototype contributes to create awareness to Muslims on the importance of straightening “saf” during congregational prayers.